2012
DOI: 10.1111/j.1467-6486.2012.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Capital Is Not Enough: Innovation in Developing Economies

Abstract: Economic development and social entrepreneurship often conceive of poverty as a resource allocation problem in which a lack of capital prevents the poor from increasing their income through entrepreneurship. This allocative view, however, represents only one possible approach to conceptualizing entrepreneurial opportunity. The alternative discovery-and creativity-based views place a greater emphasis on innovation which implies that superior ideas are also needed if poverty is to be reduced through firm perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
217
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(251 citation statements)
references
References 138 publications
5
217
0
2
Order By: Relevance
“…A Larger proportion of skilled employees in the firms is associated with innovation activities, and the correlation is significant for both technological and non-technological innovations. This supports Bradley et al (2012) study of Kenyan firms in which education and human capital were the main constraints to innovation. Competition seems to be a driver of innovation as well in the Ghanaian firms, pushing firms that work in competitive markets to innovate in order to remain in business.…”
Section: Innovation Activities In Low-income Countriessupporting
confidence: 67%
See 1 more Smart Citation
“…A Larger proportion of skilled employees in the firms is associated with innovation activities, and the correlation is significant for both technological and non-technological innovations. This supports Bradley et al (2012) study of Kenyan firms in which education and human capital were the main constraints to innovation. Competition seems to be a driver of innovation as well in the Ghanaian firms, pushing firms that work in competitive markets to innovate in order to remain in business.…”
Section: Innovation Activities In Low-income Countriessupporting
confidence: 67%
“…The level of education of entrepreneurs is regarded as an important, although not a sufficient, condition for innovation. Bradley et al (2012) advocate that capital is not a "silver bullet", and education and human capital are the major constraints of innovation in Kenyan small firms. The lack of resources in the education system in many LICs makes the non-formal training the main source for learning, together with 'learning by doing' (Oyelaran-Oyeyinka and Lal, 2006).…”
Section: Informality Innovation and Firms' Growthmentioning
confidence: 99%
“…In research by Bradley et al [4] they concluded that capital alone is not a 'silver bullet' for the problem of poverty in developing economies. They have shown that, similar to developed nations, innovation is necessary for microcredit businesses to achieve fi rm performance, which contribute to increases in income and standards of living.…”
Section: Resultsmentioning
confidence: 99%
“…Bradley et al [49] 43 show that innovation ensures that a firm enhances its performance, especially on profits. Creating new products keeps on satisfying customer desires.…”
Section: The Perspective Of Profit and New Productmentioning
confidence: 99%